Pagdating sa dulo - Gomez, Rita; Vargas, Vic; Garcia, Eddie (1971)
A taxi dancer (Rita Gomez) and taxi driver (Vic Vargas) are fished out of poverty and anonymity by a commercial film director (Eddie Garcia). The obsession with success forces them to affect images as movie stars, which suppress and eventually destroy them as persons and lovers.520